1978
DOI: 10.2337/diacare.1.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem and Depression in Adolescent Diabetic Girls

Abstract: This investigation was designed to examine self-esteem and depression in diabetic adolescent girls. One hundred nondiabetic girls age 12-16 and 105 diabetic girls age 12-16 were administered the Rosenberg Self-Esteem Scale and the Beck Depression Inventory. Results indicated no significant difference between diabetic and nondiabetic girls in self-esteem scores. Diabetic girls showed significantly more depression than nondiabetic girls. Close examination of results revealed that, in fact, diabetic and nondiabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…Conversely, the self-esteem of non-obese IDDM seemed to be quite as good as that of normal girls, and obese IDDM girls had better self-esteem scores than did non-IDDM obese girls. These results confirm that IDDM, unlike obesity (Krasnerger et al, 1988), need not lead to a lower self-esteem (Sullivan, 1978;Kovacs et al, 1990). The difference should not be linked to greater obesity in non-diabetic girls, that is responsible for more social problems, since the excess weight of the two groups did not differ significantly.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…Conversely, the self-esteem of non-obese IDDM seemed to be quite as good as that of normal girls, and obese IDDM girls had better self-esteem scores than did non-IDDM obese girls. These results confirm that IDDM, unlike obesity (Krasnerger et al, 1988), need not lead to a lower self-esteem (Sullivan, 1978;Kovacs et al, 1990). The difference should not be linked to greater obesity in non-diabetic girls, that is responsible for more social problems, since the excess weight of the two groups did not differ significantly.…”
supporting
confidence: 76%
“…Some studies have found that obese subjects have a bad self-esteem and more emotional disorders (IsnardMugnier et al, 1993). Other studies have found that emotional disorders are more common in adolescent IDDM girls (Sullivan, 1978;Simonds et al, 1981;Close et al, 1986;Kovacs et al, 1990), but they assessed anxious and depressive dimensions and did not diagnose DSM-III-R anxiety disorders or depression. Hence, we evaluated self-esteem and emotional disorders in the populations of IDDM and non-diabetic, obese and non obese, adolescent girls.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies (12) suggest that self-esteem is not more impaired and depressive symptoms are not more common in adolescent girls with IDDM, other research suggests that subtle disturbances may be present. For example, Hauser et al (13) found that ego development and self-image complexity are impaired in adolescents with IDDM compared with similar nondiabetic individuals.…”
Section: Self-reported Psychological Disturbances In Iddm Patients Comentioning
confidence: 96%
“…The sources of depression have included fear of diabetic complications, anxiety about an early death, and frustration of possible future deterioration (Hauser and PoUets 1979;Koch and Molar 1974;Sullivan 1978). Menninger (1935) suggested that a diabetic personality characterised diabetic patients.…”
Section: Psychosodal Ai^ects Of Diabetesmentioning
confidence: 99%